2021
DOI: 10.1016/j.eclinm.2021.100795
|View full text |Cite
|
Sign up to set email alerts
|

Stratified care to prevent chronic low back pain in high-risk patients: The TARGET trial. A multi-site pragmatic cluster randomized trial

Abstract: Background: Many patients with acute low back pain (LBP) first seek care from primary care physicians. Evidence is lacking for interventions to prevent transition to chronic LBP in this setting. We aimed to test if implementation of a risk-stratified approach to care would result in lower rates of chronic LBP and improved self-reported disability. Methods: We conducted a pragmatic, cluster randomized trial using 77 primary care clinics in four health care systems across the United States. Practices were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 40 publications
3
83
1
1
Order By: Relevance
“…Our findings did not reflect the results of the STarT Back trial. The findings were more in line with the US MATCH study (Cherkin et al., 2018 ) and the TARGET study (Delitto et al., 2021 ), in which the intervention arm did not have a significant effect on patient outcomes, healthcare use or the development of chronic LBP, compared to the control arm.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings did not reflect the results of the STarT Back trial. The findings were more in line with the US MATCH study (Cherkin et al., 2018 ) and the TARGET study (Delitto et al., 2021 ), in which the intervention arm did not have a significant effect on patient outcomes, healthcare use or the development of chronic LBP, compared to the control arm.…”
Section: Discussionsupporting
confidence: 81%
“…At the conclusion of the trial, patients in the PIPT intervention group showed no differences in disability, care utilization, or transition to chronic low back pain. 20 An earlier study, the MATCH trial (6 primary care clinics, n = 603 enrolled patients), investigated whether use of the STarT Back risk-stratification strategy for patients with low back pain resulted in superior outcomes for physical function and pain severity. 21 While clinicians used the STarT Back tool with half of participants, use of the tool did not change recommended treatments nor did the intervention have any significant effects on patient outcomes.…”
Section: Dovepressmentioning
confidence: 99%
“…In TARGET, the authors report a significant "implementation shortfall" with the PIPT referral process resulting in only half of the patients in the stratified care group receiving a PIPT referral. 20 This implementation shortfall was attributed to electronic health record challenges with the referral process to PIPT clinicians, as well as a lack of study-funded resources for physical therapy visits. 20 Similarly, in MATCH, the authors discuss implementation difficulties due to the complexity of the PIPT intervention, as well as the nuances of the US healthcare system, when compared to the U.K. 21 Accordingly, this perspective addresses issues of PIPT implementation within US health systems.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations